2009
DOI: 10.1073/pnas.0912673106
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in supercoiling drive circadian gene expression in cyanobacteria

Abstract: The cyanobacterium Synechococcus elongatus PCC 7942 exhibits oscillations in mRNA transcript abundance with 24-h periodicity under continuous light conditions. The mechanism underlying these oscillations remains elusive-neither cis nor trans-factors controlling circadian gene expression phase have been identified. Here, we show that the topological status of the chromosome is highly correlated with circadian gene expression state. We also demonstrate that DNA sequence characteristics of genes that appear monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
239
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(253 citation statements)
references
References 35 publications
8
239
0
Order By: Relevance
“…These constructs are readily prepared using standard molecular biology techniques, as described in SI Text. Accurate quantitative models of sequence-dependent structural transitions are needed to explain sophisticated cellular functions such as supercoiling-dependent regulation of gene expression profiles (5,6). In three divergent examples, we found that the behaviors of short regions of homogenous sequences were well described by a model for cooperative structural transitions in polymers, allowing the extraction of thermodynamic parameters relevant to sequence-dependent torsional responses (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These constructs are readily prepared using standard molecular biology techniques, as described in SI Text. Accurate quantitative models of sequence-dependent structural transitions are needed to explain sophisticated cellular functions such as supercoiling-dependent regulation of gene expression profiles (5,6). In three divergent examples, we found that the behaviors of short regions of homogenous sequences were well described by a model for cooperative structural transitions in polymers, allowing the extraction of thermodynamic parameters relevant to sequence-dependent torsional responses (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The sequence dependence of stress-induced destabilization (2) has been hypothesized to affect the specific localization of replication initiation (3,4) and the variable response of transcriptional promoters (5). Supercoiling can lead to either activation or repression of transcription, and promoter-specific responses are exploited by organisms that use supercoiling as a global regulator of changing transcriptional programs (6). In addition to strand separation, superhelical tension may also be released by the formation of Z-DNA, a left-handed double-helical structure (7,8).…”
mentioning
confidence: 99%
“…Moreover, one would need to bring kaiBC expression under the control of a promoter that is constitutively active. However, most promoters of S. elongatus (37,43), and even many heterologous promoters from Escherichia coli (52), are influenced by the circadian clock. Nevertheless, a number of promoters have been reported that exhibit arrhythmic activity (43), and these might be possible candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TTC is much less well understood than the PPC, recently much progress has been made (37)(38)(39). In particular, several proteins important for transcriptional regulation of the kaiBC operon have now been identified.…”
Section: A Ppc-in Vitro: a Protein Phosphorylation Cycle With Constamentioning
confidence: 99%
“…The cyanobacterial circadian oscillator (3), composed of only three proteins-KaiA, KaiB, and KaiC (4)-sustains an ordered pattern of KaiC autophosphorylation and autodephosphorylation (5). This oscillator governs circadian rhythms of gene expression (6,7) and chromosome compaction (8)(9)(10), and gates cell division (11)(12)(13).…”
mentioning
confidence: 99%